Efektivitas Penggunaan Aplikasi Srikandi melalui Pendekatan Model Kesuksesan Sistem Informasi Delone dan Mclean di Instansi Pemerintahan Sekretariat DPRD Kabupaten Pesisir Selatan - Fadly Gapanwa; Marlini Marlini (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
This study aims to analyze the effectiveness of using the Integrated Dynamic Archival Information System (SRIKANDI) at the Secretariat of the Regional House of Representatives (DPRD) of Pesisir Selatan Regency. SRIKANDI is a national archival application developed by the Government of Indonesia as part of the implementation of the Electronic-Based Government System (SPBE). This research employs a qualitative approach with a descriptive method through in-depth interviews and observations of SRIKANDI users within the Secretariat of the DPRD of Pesisir Selatan Regency. The theoretical framework applied is the DeLone and McLean Information System Success Model (2003), which includes dimensions of system quality, information quality, service quality, system use, user satisfaction, and net benefits. The findings indicate that the implementation of SRIKANDI has made a positive contribution to improving the efficiency of archival and correspondence management at the Secretariat of the DPRD of Pesisir Selatan Regency, with a 40% increase in administrative process speed and a 55% reduction in paper usage. However, several challenges remain, including limitations in information technology infrastructure, gaps in digital literacy among senior staff, and suboptimal integration with other information systems. This study recommends the need for continuous intensive training, enhancement of IT infrastructure, and the development of more user-friendly application features to maximize the benefits of SRIKANDI in supporting effective and accountable governance.